A Review on Affordable Combinations in Type 2 Diabetes Care: Exploring the Cost-Effective Potential of Glipizide + Metformin and Glimepiride + Metformin + Pioglitazone - Shaikh, Shehla; Vaidya, Vishal; Gupta, Amit; Kulkarni, Raghunath; Joshi, Ashok; Kulkarni, Medhinee; Sharma, Vidhe; Revankar, Santosh (Curēus (Palo Alto, CA), 2024)
Management of type 2 diabetes mellitus (T2DM) largely relies on medication adherence of individuals with diabetes to achieve optimal glycemic control. The economic burden of diabetes could impede adherence, leading to a reduction in treatment efficacy and increased risk of complications. Furthermore, monotherapy in diabetes is losing traction due to its ineffectiveness in achieving early and sustained optimal glycemic control in a significant proportion of the population. Hence, clinicians prefer combination treatment due to their improved efficacy and safety. Considering these factors, the current review highlights the safety and efficacy of the affordable combination therapies, a dual therapy, glipizide + metformin, and a triple-drug combination of glimepiride + metformin + pioglitazone and its applicability in the management of T2DM among individuals with diabetes in India.